Gender Nonconforming Children. Issue 6 (November 2015) - Unknown
Abstract : How should pediatric nurses handle parents' questions about gender nonconformity in children and adolescents? Our pediatric nursing expert, Dr. Beal, offers suggestions based on the most recent evidence.